Analysis on Generational Shift and Evolution Trend of Geological Tourism Products in Yunnan. (January 2019) - Chang, Chen
Abstract: Tourism products have a certain life cycle and internal upgrading needs. The form of geological tourism products is relatively stable and also has a relatively long life cycle. Meanwhile, its internal upgrading which manifests as generational shift is obvious and frequent. Such factors as what noticeable generational shift of Yunnan geological tourism products is; how to distinguish and link up different generational tourism products; what are the internal causes and external causes leading to the generational shift, what is the trend of the development of geological tourism products in Yunnan are worthy of in-depth discussion and analysis.